Decision-Support Tool for the Establishment of Contracts in the Electricity Market - Azevedo, Filipe (2003)
The Pool, in many countries, was adopted for the participants of the electricity market to trade the electrical energy in a basis of each half-hour or one hour of the next day. However, like the traditional markets, the agents of electrical market are now exposed to the volatility of market price. In some countries, to face that problem and to turn the market more liquid, the derivatives markets – futures and options - were introduced to negotiate products with electrical energy as underlying active. In this context, there is a need of decisionsupport tools to assist those agents for the use of derivatives markets with the objective of practicing the hedge. In this paper, we present a decision model that supports producers to establish contracts with the objective to maximize the profit expected utility.